Stalking z perspektywy sprawcy i ofiary - Malicka-Ochtera, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Stalking as a crime has been punishable under Polish law since 2011. Etymologic-ally, the term comes from the word “to stalk” — tracking. The criminal perpetrator of the crime violates the social order by violating its rules, motivated by the desire to take control of the victim. The basis of the stalker’s causative actions are usually strong emo-tions such as love, hate or revenge. The victim is a person who most often has or had a personal relationship with the perpetrator, for example a former partner who ended the relationship. The primary effect on the victim’s psyche is fear, anxiety, and a sense of danger, followed by mental disorders and even death by murder or suicide. The feeling of social disorder occurs on both the perpetrator’s and victim’s side. The phenomenon of stalking is plastic, because depends on the boundaries set by norms and values recognized in society.
Keywords: prześladowanie; stalking; cyberstalking; sprawca przestępstwa; ofiara; bezpieczeństwo